2008
DOI: 10.1007/s00203-008-0426-y
|View full text |Cite
|
Sign up to set email alerts
|

Stress tolerance, genetic analysis and symbiotic properties of root-nodulating bacteria isolated from Mediterranean leguminous shrubs in Central Spain

Abstract: Nine root-nodulating bacterial isolates were obtained from the leguminous shrubs Spartium junceum, Adenocarpus hispanicus, Cytisus purgans, Cytisus laburnuum, Retama sphaerocarpa and Colutea arborescens in areas of Central Spain. A poliphasic approach analyzing phenotypic, symbiotic and genetic properties was used to study their diversity and characterize them in relation to Mediterranean conditions. Stress tolerance assays revealed marked variations in salinity, extreme pH and cadmium tolerance compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 33 publications
6
45
0
Order By: Relevance
“…Our results are in accordance with other previous investigations on the association between rhizobia and Retama from different Mediterranean areas (Spain, Algeria and Morocco); it has been noticed that Bradyrhizobium is the dominant genus of symbiotic nitrogen fixing bacteria associated with Retama species (Rodríguez-Echeverría et al, 2003Ruiz-Díez et al, 2009;Boulila et al, 2009;Guerrouj et al, 2013). The previous report on nodule isolates from R. raetam growing in arid areas of Tunisia yielded very contrasting results (Mahdhi et al, 2008).…”
Section: Morphological and Cultural Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in accordance with other previous investigations on the association between rhizobia and Retama from different Mediterranean areas (Spain, Algeria and Morocco); it has been noticed that Bradyrhizobium is the dominant genus of symbiotic nitrogen fixing bacteria associated with Retama species (Rodríguez-Echeverría et al, 2003Ruiz-Díez et al, 2009;Boulila et al, 2009;Guerrouj et al, 2013). The previous report on nodule isolates from R. raetam growing in arid areas of Tunisia yielded very contrasting results (Mahdhi et al, 2008).…”
Section: Morphological and Cultural Characteristicssupporting
confidence: 92%
“…It has been noticed that Bradyrhizobium is the dominant genus of symbiotic nitrogen-fixing bacteria associated with Retama species: Retama monosperma (L.) Boiss., Retamaraetam Webb and Berthel., Retama sphaerocarpa Boiss. (Rodríguez-Echeverría et al, 2003Ruiz-Díez et al, 2009;Boulila et al, 2009;Guerrouj et al, 2013). Recently, the novel B. retamae species, which groups with B. elkanii and B. pachyrhizi and related B. lablabi and B. jicamae type strains included in Bradyrhizobium group II ( Menna et al, 2009), has been isolated from R. sphaerocarpa and R. monosperma in Morocco and Spain (Guerrouj et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The groups formed had between 26 % (group D) and 48 % (group C) of similarity. Genetic differences between rhizobium isolates using ARDRA were also observed by Han et al (2008), Stocco et al (2008), Ruiz-Díez et al (2009) and Sui et al (2009).…”
Section: Amplified Ribosomal Dna Restriction Analysis (Ardra)mentioning
confidence: 58%
“…Tolerance to alkaline pH could be related to the calcareous and dry soils from which these isolates were isolated. However, some investigators found no correlation between the pH of the soil from which the organism was isolated and it is tolerant to different levels of pH in growth medium [43]. Bradyrhizobium strains native to tropical soils, grow at different pH levels and optimal growth occurs at pH 6.0, indicating that they are adapted to slightly acidic conditions [44].…”
Section: Symbiotic and Phenotypic Characteristics Of Rhizobia Nodulaimentioning
confidence: 99%